2008
DOI: 10.1038/jcbfm.2008.94
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 Signaling in Brain Endothelial Cells

Abstract: NRG1 signaling has multiple functions in neurons and glia. The data in this study demonstrate that NRG1 may also possess significant signaling and cytoprotective properties in human brain endothelial cells (BMECs). NRG1 mRNA and protein expression are present in these cells, and NRG1 receptors erbB2 and erbB3 are phosphorylated in response to NRG1. NRG1 triggers clear biological responses in BMECs – elevated phospho-Akt levels, increased ring formation in a Matrigel assay, and decreased cell death after oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 15 publications
5
32
0
Order By: Relevance
“…S1). The erbB receptor complement of EPCs (erbB2ϩ/ erbB3ϩ/erbB4Ϫ) is consistent with that of mature ECs (8,27). Another interesting similarity is that eEPCs, like mature ECs, express NRG-1 ligand.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…S1). The erbB receptor complement of EPCs (erbB2ϩ/ erbB3ϩ/erbB4Ϫ) is consistent with that of mature ECs (8,27). Another interesting similarity is that eEPCs, like mature ECs, express NRG-1 ligand.…”
Section: Discussionsupporting
confidence: 62%
“…Although upregulation of VEGF expression may, in part, explain the NRG-dependent angiogenic effect, there is evidence for a VEGF-independent effect of NRG on angiogenesis (35). In human brain microvascular ECs NRG treatment protects against oxidant injury, indicating that NRG regulates endothelial homeostasis in "normal" (e.g., noncancerous) tissues as well (27). These data indicate a potential role for NRG/erbB signaling in regulation of vascular homeostasis.…”
mentioning
confidence: 95%
“…ErbB receptors are expressed in EPCs, and NRG-1 stimulation can enhance EPCs survival and their participation in angiogenic responses [28]. Lok et al reported that NRG-1 can decrease human brain endothelial cells death after oxidative injury with H 2 O 2 [29]. Oxidative stress caused by mitochondrial superoxide overproduction in endothelial cells is the major mechanism in the development of vascular complications in diabetes [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…58,59 NRG-1β exerts a cytoprotective effect against oxidant injury in multiple cell types in the brain, including the microvascular endothelial cell. 60 …”
Section: Nrg In the Central And Peripheral Nervous System: Implicatiomentioning
confidence: 99%